Fearless leadership : how to overcome behavioral blind spots and transform your organization - Malandro, Loretta A. (McGraw Hill-Ascent Audio, 2009)
Do you want to move your company in a new direction? Fearless Leadership provides you with the tools to successfully drive change, overcome obstacles, and engage and align people in working effectively together to achieve your business objectives. Leadership guru Dr. Loretta Malandro has developed a groundbreaking behavior-based methodology that is used around the globe to create top-performing leaders and high-performance organizations. It is based on a simple but profound concept: In order to change your organization, you must be willing to alter your behavior and help others make the choice to change their behavior. This means demanding 100% accountability from your people--and yourself. In today's ultra-competitive business environment, a new leadership approach is needed. Fearless Leadership takes you step by step through the process of raising behavioral standards that directly impact the bottom line. You will learn the secrets behind: Confronting the blind spots that sabotage success Overcoming the success-strangling "need to be right" Eliminating silo mentality and building committed partnerships Ending compliance and gaining full support and alignment Talking straight and confronting difficult situations head on Building a culture of 100% accountability Too many people in leadership positions attempt to enact change through systemic means, such as restructuring or altering processes. The secret to real and lasting change lies in changing behavior--how people work together. Change the level of ownership and performance of people and you will transform your organization. Leaders who are able to act courageously when faced with uncertainty or fear, take bold stands, and engage with people in very real ways are those who generate great and long-lasting results. Fearless Leadership shows you how